The congrid eel genus Ariosoma in Taiwan (Anguilliformes: Congridae), with description of a new species - Smith, David G.; Ho, Hsuan-Ching; Huang, Jian-Fu; Chang, Yong-Hsu (Zootaxa, 2018)
A review of the congrid eel genus Ariosoma in Taiwan is provided. Eight species are recognized, including A. anago (Temminck & Schlegel, 1846), A. dolichopterum Karmovskaya, 2015, A. fasciatum (Günther, 1872), A. majus (Asano, 1958), A. megalops Fowler, 1938, A. meeki (Jordan & Snyder, 1900), A. shiroanago (Asano, 1958) and a new species which is described based on types and non-types collected from off southwestern Taiwan. These species can be distinguished from each other by the coloration, numbers of head pores, lateral-line pores and vertebrae. A key to all Taiwanese Ariosoma species is provided.